Developing Faith-Based Health Promotion Programs that Target Cardiovascular Disease and Cancer Risk Factors - Burchenal, Clare (Journal of religion and health, 2022)
The aim of this study was to evaluate the impact of a faith-based health promotion program on the ideal health behaviors shared between cardiovascular disease (CVD) and cancer. The primary purpose was to measure the individual-level change in three categories of shared risk behaviors between CVD and cancer (body weight, physical activity, and nutrition) among program participants. Additionally, we evaluated the association of churches' perceived environmental support on these ideal health behaviors. Baseline and 10-week surveys were conducted to assess BMI, ideal health behaviors (diet and physical activity), and a Healthy Lifestyle Score (HLS) was created to measure adherence to health behaviors. A Supportive Church Environment Score (SCES) was designed to address the second objective. Psychosocial factors (stress and coping skills) and demographics were also measured. The percentage of participants meeting diet and exercise recommendations significantly increased with the completion of the program. Whole-grain intake increased by 64% (p = 0.085), vegetable intake increased by 58% (p =  < 0.001), fruit intake increased by 39% (p =  < 0.001), physical activity increased by 14% (p =  < 0.001), and red meat consumption decreased by 19% (p =  < 0.001). The median HLS increased from 7 to 8 (p =  < 0.001). At baseline the association between ideal health behaviors and the SCES was significant for fruit intake (r = 0.22, p-value = 0.003) and red meat consumption (r = 0.17, p-value = 0.02). The aggregate behaviors as represented by the HLS were associated with the SCES (r = 0.19, p-value = 0.03). The significant increase in the HLS indicates an average improvement in the degree to which participants were meeting recommendations after completing the program. Therefore, adherence to these ideal health behaviors increased over the 10-week program.